'Pretty fit and healthy': The discussion of older people in cancer multidisciplinary meetings. Issue 1 (January 2019) - Lane, Heather P.; McLachlan, SueAnne; Philip, Jennifer A.M.
Abstract: Introduction: Cancer multidisciplinary meetings (MDMs) are central to treatment decision making. The language used in MDMs may influence treatment decisions, yet has received little research attention. This study aimed to examine the terminology used to describe non-cancer items in the discussion of older people within cancer MDMs. Methods: MDMs of four tumour streams were attended over twelve weeks. For each person aged 70 or older discussed, the following was hand recorded: age, gender, and phrases describing non-cancer items and patient views. A qualitative thematic analysis was employed to examine the text. Results: Twenty cancer MDMs were attended, at which 71 people aged 70 or older were discussed. Age, comorbid medical conditions, and general descriptors emerged as the areas in which non-cancer information was presented. In contrast to the medical terminology used to describe comorbid medical conditions, non-specific general descriptors, such as 'fit', 'well', and 'good', were used to describe other aspects of older people. Adverbs, including 'very', 'pretty', and 'quite', often accompanied general descriptors. The, often subtle, intonation and context associated with these adverbs resulted in markedly different meanings. Conclusion: Non-objective, potentially ambiguous general descriptors were commonly used to encompass non-disease aspects of older people in cancer MDMs. These descriptors may have the potential to sway treatment recommendations. However, their frequent use suggests team members recognise that non-disease aspects of a person, aside from chronological age, are considerations in treatment recommendations. Therefore, strategies to increase discussion of non-cancer items in a more objective manner may be acceptable to MDM attendees.